The "Problem of Extension" revisited: new modes of digital participation in science - Sascha Dickel; Martina Franzen (Journal of science communication, 2016)
Citizen Science is part of a broader reconfiguration of the relationship between science and the public in the digital age: Knowledge production and the reception of scientific knowledge are becoming increasingly socially inclusive. We argue that the digital revolution brings the “problem of extension” — identified by Collins and Evans in the context of science and technology governance — now closer to the core of scientific practice. In order to grasp the implications of the inclusion of non-experts in science, the aim of this contribution is to define a role-set of non-certified knowledge production and reception, serving as a heuristic instrument for empirical clarifications. – – Citizen Science ist Teil einer Rekonfiguration des Verhältnisses von Wissenschaft und Öffentlichkeit im Kontext des digitalen Wandels: Sowohl die Produktion als auch die Rezeption wissenschaftlicher Ergebnisse werden sozial inklusiver. Damit aber stellt sich das ,,problem of extension“, das Collins und Evans im Hinblick auf die wissenschaftliche Politikberatung ausgemacht haben, nun in neuer Weise. Es betrifft nicht mehr nur Fragen politischer Partizipation, sondern wird im Zuge des digitalen Wandelns nun auch im Kernbereich wissenschaftlicher Tätigkeit relevant. Ziel dieses Beitrags ist die Definition eines Rollen-Sets nicht-zertifizierter Wissensproduktion und -rezeption, das als heuristisches Instrument weitere empirische Forschung anregen soll, um die Implikationen der sozialen Inklusion von Nicht-Professionellen in die Wissenschaft genauer zu eruieren.
Keywords: 330; Citizen science; Participation and science governance; Social inclusion